2015
DOI: 10.15578/iaj.10.1.2015.19-31
|View full text |Cite
|
Sign up to set email alerts
|

EMBRYONIC AND LARVAL DEVELOPMENT OF A RED STRAIN OF THE EGYPTIAN AFRICAN CATFISH (Clarias gariepinus Burchell, 1822)

Abstract: Egyptian African catfish is one of several African catfish (Clarias gariepinus) strains introduced to Indonesia. Several breeding activities using that strain in Sukamandi resulted in some individuals with redish-yellow body colour (a red strain). Biological informations related to aquacultural aspects of that red strain were still scarce. The present study aimed to elucidate the embryonic and larval developments of the red strain compared to those of the black (normal coloured) one, using the progenies obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
3
3
0
2
Order By: Relevance
“…In another study, the optimal range for temperature (29–31 °C), DO (5.0–6.0 mg/L), and pH (7.1–7.5) was reported for the spawning of stinging catfish [ 31 ]. An incubation temperature of 27.0–29.5 °C was also recorded for embryonic development of the Egyptian African catfish [ 32 ], which corresponds to the readings of this study.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In another study, the optimal range for temperature (29–31 °C), DO (5.0–6.0 mg/L), and pH (7.1–7.5) was reported for the spawning of stinging catfish [ 31 ]. An incubation temperature of 27.0–29.5 °C was also recorded for embryonic development of the Egyptian African catfish [ 32 ], which corresponds to the readings of this study.…”
Section: Discussionsupporting
confidence: 80%
“…The yolk sac of M. gulio larvae was depleted on the 3rd day after hatching, at which time the larvae measured 3.86 mm in total length [ 59 ]. The yolk sacs of Clarias gariepinus were reported to be completely absorbed at about 60:00–66:00 h after hatching at a water temperature range of 25–28 °C [ 32 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, for the larval hatching stage, the average time required for G 3 embryos to hatch from female A was 973 minutes (16.22 hours), female B was 985 minutes (16.42 hours) and C 996 minutes (16.60 hours) (Figure 3). Whereas, hatching of non-transgenic catfish (C. gariepinus) eggs was 1040 minutes (17.33 hours) and for Egyptian African catfish (C. gariepinus) eggs it was 1080 minutes (18 hours) [11] . Comparison of hatching duration of catfish eggs between transgenic and non-transgenic fish showed that the hatching rate of transgenic fish eggs was 1-1.5 hours faster than that of non-transgenic fish, indicating that GH-transgenesis (CgGH) was induced embryo development and hatching of fish eggs.…”
Section: Hatching Rate Of the G3 Mutiara Catfish Eggmentioning
confidence: 98%
“…Hasil-hasil penelitian karakterisasi morfometrik yang telah dilakukan pada ikan lele Afrika albino yang lain menunjukkan hasil serupa. Ikan lele Afrika albino yang berasal dari Mesir (Iswanto et al, 2016) dan Thailand (Iswanto et al, 2020b)…”
Section: Karakteristik Biometrik-morfologisunclassified
“…Serupa dengan ikan lele Mutiara albino, ikan lele Afrika albino yang berasal dari Mesir (Iswanto et al, 2016) dan Thailand (Iswanto et al, 2020b) juga memiliki jumlah jari-jari sirip punggung dan sirip dubur yang lebih sedikit dibandingkan yang berwarna normal. Hasil-hasil penelitian tersebut mengindikasikan bahwa albinisme pada spesies ikan lele Afrika tampaknya juga berkaitan dengan karakteristik meristiknya, yakni menyebabkan ikan lele Afrika albino memiliki jumlah jari-jari sirip punggung dan sirip dubur yang lebih sedikit dibandingkan yang berwarna normal.…”
Section: Ikan Lele Mutiara Mutiara African Catfishunclassified